A review on organic nanoparticle-based optoelectronic devices: from synthesis to applications - Liu, Zhe; Xie, Chen; Heumueller, Thomas; McCulloch, Iain; Brabec, Christoph J; Huang, Fei; Cao, Yong; Li, Ning (Energy & environmental science, 2025)
Over the past few decades, organic optoelectronic devices have shown broad application prospects. However, the solubility of organic materials requires the use of toxic solvents, hindering the fabrication of these devices in an air environment. Furthermore, the common approaches such as exploring non-halogenated solvents and side-chain modification do not address the root of this problem. In this case, considering the increasing focus on the subject of nanoparticles, dispersing organic materials as nanoparticles in non-toxic water/alcohol solvents provides a perfect and universally applicable solution to address the toxicity problem. In addition, the unique properties of nanoparticles can provide new ideas for the optimization and tuning of organic optoelectronic devices. In this review, we present an up-to-date overview of the water/alcohol-based organic nanoparticles applied in optoelectronic devices, encompassing the entire journey from nanoparticles to practical applications, which is partitioned into four vital segments: nanoparticle intrinsic property, from organic semiconducting materials to nanoparticles, organic thin films, and finally device applications. An overview of water/alcohol-based organic nanoparticles applied in optoelectronic devices, encompassing the entire journey from nanoparticle synthesis to practical applications.